Issues Of Criminal-Law Protection Of Intellectual Property Rights - Kholiknazarov Farhod Bozor ogli (Emerging Frontiers Library for The American Journal of Political Science Law and Criminology, 2025)
This article analyzes the theoretical and practical aspects of the criminal-legal protection of intellectual property rights. The content of the norms related to the protection of authors’ and related rights in the Constitution and the Criminal Code of the Republic of Uzbekistan is revealed. Furthermore, a comparative analysis is conducted of the differences in approaches to establishing criminal liability for infringements of intellectual property rights in national and foreign legal systems. The article emphasizes that although criminal liability measures play an important role in protecting intellectual property rights, their punitive nature alone cannot fully resolve the problem. In this regard, the necessity of forming a comprehensive protection system and effectively applying civil and administrative measures in the field of intellectual property is scientifically substantiated. The study also examines the experiences of countries such as Georgia, Kazakhstan, Russia, Germany, Italy, and France, and presents conclusions and recommendations for improving national legislation.